Brain-Computer Interfacing for Intelligent Systems - Nijholt, Anton; Tan, Desney; Pfurcheller, Gert; Brunner, Clemens; Millan, Jose del R; Allison, Brendan; Graimann, Bernhard; Popescu, Florin; Blankertz, Benjamin; Muller, Klaus-Robert (IEEE Intelligent Systems, 2008)
Advances in cognitive neuroscience and brain-imaging technologies give us the unprecedented ability to interface directly with brain activity. These technologies let us monitor the physical processes in the brain that correspond with certain forms of thought. Driven by society’s growing recognition of the needs of people with physical disabilities, researchers have begun using these technologies to build brain-computer interfaces (BCIs) communication systems that don’t depend on the brain’s normal output pathways of peripheral nerves and muscles.